ANALISIS MINAT BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI KELAS V SD NEGERI PEUNAGA CUT UJONG KECAMATAN MEUREUBO - Nurjannah; Niken Saputri; Dian Kristanti (Jurnal Binagogik, 2025)
This research aims to describe students' interest in learning through the Problem Based Learning (PBL) learning model in Class V of Peunaga Cut Ujong State Elementary School, Meureubo District. The type of research used is descriptive qualitative research. The subjects taken in this research were all fifthgrade students at Peunaga Cut Ujong State Elementary School, with a total of 15 students. The instruments used to collect data in this research consisted of observation sheets, interview sheets, questionnaire sheets and validation sheets. The results of this research can be concluded that students' interest in learning through the Problem Based Learning (PBL) learning model in Class V of Peunaga Cut Ujong State Elementary School, Meureubo District. from the students' answers to the question items in the questionnaire which shows the percentage of students who got good criteria, there were 9 students, 60.00%, there were 5 students, 33.33% for quite good criteria, and 1 student for poor criteria, 06, 67% indicated that the use of the Problem Based Learning learning model also sparked students' interest in learning about the human respiratory system.